Transplant versus resection for the management of hepatocellular carcinoma meeting Milan Criteria in the MELD exception era at a single institution in a UNOS region with short wait times. Issue 6 (17th December 2013) - Squires, Malcolm H.; Hanish, Steven I.; Fisher, Sarah B.; Garrett, Cristen; Kooby, David A.; Sarmiento, Juan M.; Cardona, Kenneth; Adams, Andrew B.; Russell, Maria C.; Magliocca, Joseph F.; Knechtle, Stuart J.; Staley, Charles A.; et al.
<x xml:space="preserve">Abstract</x> Background Management of hepatocellular carcinoma (HCC) in the Model for End‐Stage Liver Disease (MELD) exception era remains regionally variable. Outcomes were compared for patients undergoing transplant versus resection at a single institution in a UNOS region with short wait times for organ availability. Methods All patients who underwent resection of HCC from January 2000 to August 2012 and patients who underwent transplant post‐January 2006, during the Milan Criteria (MC)‐based MELD exception policy for HCC, were identified. Primary outcomes were overall survival (OS) and recurrence‐free survival (RFS). Results Two hundred fifty‐seven patients were analyzed, of whom 131 underwent transplant and 126 underwent resection. All transplant patients met MC; 45 (36%) resection patients met MC. Median follow‐up time was 30 months. Median wait time to transplant was 55 days; no patients dropped off the waitlist while awaiting an organ. Among patients meeting MC, transplant demonstrated significantly greater 5‐year OS (65.7% vs. 43.8%; P = 0.005) and RFS (85.3% vs. 22.7%; P < 0.001) versus resection. For patients with hepatitis C, transplant (n = 87) demonstrated significantly improved 5‐year outcomes compared to patients meeting MC who underwent resection (n = 21; OS: 63.5% vs. 23.3%; P = 0.001; RFS: 83.5% vs. 23.7%; P < 0.001). Conclusion In a region with short waitlist times for organ availability, liver transplant is associated with improved survival compared to resection for HCC within MC and should be considered for all patients meeting MC, particularly those with hepatitis C. J. Surg. Oncol. 2014 109:???–???. © 2013 Wiley Periodicals, Inc.